2006
DOI: 10.1175/jcli3852.1
|View full text |Cite
|
Sign up to set email alerts
|

Defining Intraseasonal Rainfall Variability within the North American Monsoon

Abstract: This study provides an empirical description of intraseasonal rainfall variability within the North American monsoon (NAM) region. Applying particular definitions to historical daily rainfall observations, it demonstrates that distinct intraseasonal rainfall modes exist and that these modes differ considerably from the monsoon core region in northwest Sonora (SON), California, to its northward extension in southeast Arizona (AZ). To characterize intraseasonal rainfall variability (ISV), separate P-mode princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
4
23
0
Order By: Relevance
“…2). This also agrees with the results of [36], who found that while the intensity of summer precipitation in Sonora state increased significantly since 1977, in association with the +PDO phase, the monsoon season became shorter, resulting in a non-significant upward trend in precipitation [10] (Figs 2a-c). The linear trend of the percentage contribution of P95 associated with TCs was significantly increased (0.86% decade -1 , p<0.05) during the period 1961-2000 (Fig.…”
supporting
confidence: 92%
“…2). This also agrees with the results of [36], who found that while the intensity of summer precipitation in Sonora state increased significantly since 1977, in association with the +PDO phase, the monsoon season became shorter, resulting in a non-significant upward trend in precipitation [10] (Figs 2a-c). The linear trend of the percentage contribution of P95 associated with TCs was significantly increased (0.86% decade -1 , p<0.05) during the period 1961-2000 (Fig.…”
supporting
confidence: 92%
“…For instance, Englehart and Douglas (2006) find, for Sonora, a long-term trend towards a shorter monsoon season (i.e. later starts and earlier stops).…”
Section: Streamflow Modulation By Decadal Scale Climate Variabilitymentioning
confidence: 98%
“…We completed two additional simulations over the North America Monsoon (NAM) region (23-40 • N, 121-100 • W) using 25-km grid spacing on both simulations with default and optimal parameters, respectively. The NAM represents a distinctly different climate regime compared to the SGP in the central US (Berbery, 2001;Englehart and Douglas, 2006). For example, convection in the semi-arid NAM region is associated with strong surface heating, with a dominant late afternoon precipitation maxima related to the buildup of CAPE during the day.…”
Section: Dependence Of Optimized Parameters On Climate Regimementioning
confidence: 99%